STRETCHING EFFECT ON STUDENT LEARNING CONCENTRATION - siti indatul laili; Ariu Dewi Yanti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Student activity in the learning process in the classroom sits more. Sitting long could limit blood and incoming oxygen to the brain so which affects concentration. So, therefore stretching is needed. The purpose of this research was to prove the stretching effect on student learning concentration. The design of this research used a pretest-posttest-only control group design. The population in this research were all students of class II D3 nursing STIKES Bina Sehat PPNI Mojokerto as 79 respondents. The sample of this research were all students of class II D3 nursing STIKES Bina Sehat PPNI Mojokerto 39 respondents in the experimental group and 40 respondents in a control group, with a total sampling technique. The instrument used is a questionnaire for learning concentration with test results 100% valid and reliable with = 0.881. This research was at STIKES Bina Sehat PPNI Mojokerto in Januari 2022. Data analysis using Wilcoxon signed rank test to judge the difference before and after stretching. Mann Whitney test for assessing differences in the learning concentration of the control group and experiment group with a = 0.05. The research results show, in experimental groups 20 (51%) respondents had high learning concentration before stretching and 38 (97%) respondents after stretching. Statistical Wilcoxon sign rank test results ρ = 0.00 which means that there is a stretching effect on student learning concentration. Statistical Mann-Whitney test results ρ = 0.00 means that there are differences in learning concentration in the control and experimental groups. Stretching makes the blood vessels in the muscles experience vasodilation, this makes blood flow smoother so that the muscles will also move to pump blood and oxygen to the brain which can increase learning concentration.